A mid-infrared Brillouin laser using ultra-high-Q on-chip resonators - Kiyoung Ko; Daewon Suk; Dohyeong Kim; Soobong Park; Betul Sen; Dae-Gon Kim; Yingying Wang; Shixun Dai; Xunsi Wang; Rongping Wang; Byung Jae Chun; Kwang-Hoon Ko; et al. (Nature Communications)
Abstract Ultra-high-Q optical resonators have facilitated advancements in on-chip photonics by harnessing nonlinear functionalities. While these breakthroughs, primarily focused on the near-infrared region, have extended interest to longer wavelengths holding importance for molecule science, the absence of ultra-high-Q resonators in this region remains a significant challenge. Here, we have developed on-chip microresonators with a remarkable Q-factor of 38 million at 3.86 μm wavelength, surpassing previous records by over 30 times. Employing innovative fabrication techniques, including spontaneous formation of light-guiding geometries with internal multilayer structures during material deposition, major loss factors, such as airborne-chemical absorption, were investigated and addressed. This allowed us to access the fundamental loss performance demonstrated by chalcogenide glass fibers. Leveraging this resonator, we demonstrated an on-chip Brillouin lasing in the mid-infrared with a 91.9 μW threshold power and an 83.5 Hz Schawlow-Townes linewidth. Our results showcase the effective integration of cavity-enhanced optical nonlinearities into on-chip mid-infrared photonics.